PHOTOGRAPHY AND LANDSCAPE IN ITALY IN THE 1980S: Being in a group, looking for identity. (4th May 2019) - Valtorta, Roberta
Abstract : In the 1980s and the beginning of the 1990s many Italian photographers worked so intensely on the transformation of contemporary landscape, often participating in group projects and in public commissioned projects. The phenomenon was so large and important that we can talk about an "Italian landscape photography school", although these photographers were different from one another. They were looking for a different idea of landscape, far from the stereotypes of the "Beautiful Country", as Italy is called, and far from tourist and folklore clichés. Their artistic and civil engagement contributed to change and update Italian photography and to "institutionalize" it, bringing it into public archives and museum collections.